Differential Modulating Effect of Acupuncture in Patients With Migraine Without Aura: A Resting Functional Magnetic Resonance Study - Liu, Shanshan; Luo, Shilei; Yan, Tianwei; Ma, Wen; Wei, Xiangyu; Chen, Yilei; Zhan, Songhua; Wang, Bo (Frontiers in Neurology, 2021)
Introduction: Migraine is a recurrent neurological disorder, the symptoms of which can be significantly relieved by acupuncture. However, the central mechanism via which acupuncture exerts its therapeutic effect in migraine is unclear. The aim of this study was to compare the differences in regional homogeneity (ReHo) between patients with migraine without aura (MwoA) and healthy controls (HCs) and to explore the immediate and cumulative therapeutic effect of acupuncture in patients with MwoA using resting-state functional magnetic resonance imaging (fMRI). Methods: The study subjects were 40 patients with MwoA and 16 matched HCs. The patients with MwoA received acupuncture on 2 days per week for 6 weeks for a total of 12 sessions followed by 24 weeks of follow-up. The primary clinical efficacy outcomes were the number of days with migraine and the average severity of headache. Secondary outcomes were the Migraine-Specific Quality of Life Questionnaire, Self-Rating Anxiety Scale, and Self-Rating Depression Scale scores. In the migraine group, resting-state blood-oxygen-level-dependent fMRI scans were obtained at baseline and after the first and 12th acupuncture sessions to measure the ReHo value. In the HCs, only a baseline resting-state blood-oxygen-level-dependent fMRI scan was obtained. Results: Compared with the control group, the migraine group had a significantly lower ReHo value in the cerebellum, which increased after the first acupuncture session. Long-term acupuncture significantly improved migraine symptoms and mood with a therapeutic effect that lasted for at least 6 months. After 12 acupuncture sessions, the ReHo in the cerebellum had normalized and there was significant activation of the angular gyrus in the migraine group. Conclusion: These findings suggest that migraine is related to cerebellar dysfunction. Acupuncture can improve the symptoms of migraine, normalize abnormal brain regions, and activate brain regions involved in modulation of pain. The cumulative therapeutic effect of acupuncture is more extensive and significant than its immediate effect.